Some Applications of Quasi-Subordination for Bi-Univalent Functions Using Jackson’s Convolution Operator - Atshan , Waggas Galib; Al-sajjad , Reaam Abd (Iraqi Journal of Science, 2022)
In this paper, subclasses of  the function class  ∑  of analytic and bi-univalent functions associated with operator  L_q^(k,  λ)  are introduced and defined in the open unit disk △ by applying quasi-subordination. We obtain some results about the corresponding bound estimations of the coefficients  a_(2 )  and a_(3 ).